Hydroelectric Power Station Concept Explanation in Professional Language Picture of the World (Proceedings of Southern Federal University. Philology, 2020)
The article discusses the features of the linguistic expression of the concept of a hydroelectric power station (HPS). The material for the study is the data of etymological and encyclopedic dictionaries, special educational literature, as well as data obtained during interviews of workers of various Russian hydroelectric power stations, and data from a linguistic experiment. The process of research revealed and described: etymology of the name of the concept; conceptual features of the concept; figurative layer (through the analysis of metaphorical names); evaluation layer of the concept. It has been established that the concept of hydroelectric power station (HPS) refers to gestalt concepts, since it is a conceptual system that combines different types of concepts. The professional linguistic picture of the world of hydropower is characterized by the conceptualization of the conceptual categories of «living – nonliving», «simple – complex», «natural – man-made». The axiological layer of the professional concept is poorly expressed against the background of the conceptual and figurative layers.Key words: concept, concept gestalt, professional concept, professional language picture of the world, professional sublanguage.DOI 10.18522/1995-0640-2020-2-52-62